2019
DOI: 10.1038/s41598-019-56435-6
|View full text |Cite
|
Sign up to set email alerts
|

Transition Probabilities of Noise-induced Transitions of the Atlantic Ocean Circulation

Abstract: The Atlantic Meridional Overturning Circulation (AMOC) is considered to be a tipping element of the climate system. As it cannot be excluded that the AMOC is in a multiple regime, transitions can occur due to atmospheric noise between the present-day state and a weaker AMOC state. For the first time, we here determine estimates of the transition probability of noise-induced transitions of the AMOC, within a certain time period, using a methodology from large deviation theory. We find that there are two types o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(63 citation statements)
references
References 27 publications
1
62
0
Order By: Relevance
“…Therefore, the noise is not spatially independent and the noise matrix G is no longer diagonal: it consists of a (5 × 1) row vector, with only two elements different from zero. For a reasonable choice of the parameters, the deterministic system is in a bistable regime (Castellana et al, 2019), which means that there are two possible equilibrium states under the same forcing conditions. In general, we are interested in studying transitions between the present-day AMOC (X A ) and the collapsed state (X B ).…”
Section: Transition Probabilities In a Box Model Of The Amocmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the noise is not spatially independent and the noise matrix G is no longer diagonal: it consists of a (5 × 1) row vector, with only two elements different from zero. For a reasonable choice of the parameters, the deterministic system is in a bistable regime (Castellana et al, 2019), which means that there are two possible equilibrium states under the same forcing conditions. In general, we are interested in studying transitions between the present-day AMOC (X A ) and the collapsed state (X B ).…”
Section: Transition Probabilities In a Box Model Of The Amocmentioning
confidence: 99%
“…Typical elements in the Earth's system which show multistability include the Greenland Ice Sheet (Ridley et al, 2010;Robinson et al, 2012), the Amazon Rainforest (Higgins and Scheiter, 2012;Lasslop et al, 2016) and the Atlantic Meridional Overturning Circulation (AMOC). In particular, the latter can undergo transitions to a collapsed state due to fluctuations in the surface freshwater forcing (Castellana et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For a spatially two-dimensional ocean-only model, the covariance matrices C were determined from solving a Lyapunov equation 8in Baars et al (2017) for the case of noise in the freshwater forcing. While here it served only to test the new Lyapunov equation solver (RAILS), the methodology was extended recently to compute (noise-induced) transition probabilities of the AMOC and to relate that probability to the stability indicator Σ (Castellana et al, 2019). Such transitions are thought to be involved in the Dansgaard-Oeschger (DO) events (Ditlevsen and Johnsen, 2010).…”
Section: Tipping Pointsmentioning
confidence: 99%
“…The Intergovernmental Panel on Climate Change (IPCC) Assessment Report 2013 and an increasing number of studies (Cheng et al, 2013;Rugenstein et al, 2013;Schmittner et al, 2005;Weaver et al, 2012) conclude that rapid changes in the AMOC are very unlikely to occur by the end of the 21st century, suggesting rather a slow decline from the current state (11% for RCP2.6 and 32% for RCP8.5, in the ensemble means). However, Castellana et al (2019) evaluate the risk of sudden decline and collapse of the AMOC at 15% and recent studies have revealed bias in the current climate models concerning their AMOC stability. Models have been classified as having either monostable or multistable regimes depending on the sign of their overturning-related freshwater transport at 30-32°S in the Atlantic (Weaver et al, 2012).…”
Section: Introductionmentioning
confidence: 99%